Dynamics of Recovery of Physiological Parameters After a Small-Sided Game in Women Soccer Players - Mascarin, Rafaela B.; De Andrade, Vitor L. [UNESP]; Barbieri, Ricardo A.; Loures, Joao P.; Kalva-Filho, Carlos A.; Papoti, Marcelo [UNESP] (Frontiers Media Sa, 2018)
Purpose: Training methods based on small-sided game (SSG) seem to promote physiological and tactical benefits for soccer players as they present characteristics more specific to the game. Thus, the main objective of the present study was to analyze the hormonal, biochemical, and autonomic parameters in an acute manner and the recovery dynamics (up to 72 h after) in a SSG. Methods: Thirteen professional female soccer players participated in the study (18.8 +/- 0.8 years, body mass 59.4 +/- 6.2 kg, and height 1.68 +/- 0.05 m). During and after the SSG session (4 min x 4 min separated by 3 min of passive interval and 120 m 2 coverage per player), autonomic modulation was analyzed in the time and frequency domains using heart rate variability, and blood samples (5 ml) were collected before (0 h) and after (10 min and 24, 48, 72 h) the SSG for biochemical and hormonal analysis. Results: The SSG induced an increase effect for LF (low frequency) (92,52%; Very likely increase) and a decrease effect for HF (high frequency) values (-65,72%; Very likely decrease), after 10 min of recovery. The LF/HF increase after 10 min of recovery (386,21%; Very likely increase). The RMSSD (square root of the mean squared differences of the successive N-N intervals) and pNN50 (measure of the number of adjacent NN intervals which differ by more than 50 ms) values presented a decrease effect 10 min after SSG (61,38%; Very likely decrease and-90%; Very likely decrease). The CK (creatine kinase) values presented no changes 10 min after SSG. The LDH (lactate dehydrogenase) values presented an increase effect 10 min after the SSG (19,22%; Likely increase). Both testosterone and cortisol concentrations presented the same behavior after SSG, where no alterations were observed with after 10 min (<0,37%; Most likely trivial). Conclusion: The SSG promoted significant cardiovascular stress that was restored within the first 24 h of recovery. Parasympathetic parameters continued to increase while sympathetic parameters declined significantly during the 72 h of recovery. In addition, the reduced game did not alter biochemical or hormonal responses during the 72 h.
Keywords: training; soccer; heart rate variability; muscle damage; hormone; fatigue; recovery; sport science